Evaluation of the Quality of Pharmaceutical Services Based on Minimum Service Standards at Pandanarang Boyolali Regional General Hospital in 2023 - Titianingtyas, Regita Auroraria; Nugraheni, Ambar Yunita (Universitas Muhammadiyah Gresik, 2024)
Minimum Pharmaceutical Service Standards are very important because they are performance benchmarks that are used as guidelines for pharmaceutical personnel in providing pharmaceutical services. This research aims to determine the suitability of SPM for hospitals in the pharmaceutical sector on the indicators of length of time for prescription service, customer satisfaction, and suitability of prescriptions with the formulary as well as influencing factors at the Pandanarang Boyolali Regional General Hospital in order to help the hospital in improving the quality of better pharmaceutical services. This research uses descriptive analytical research conducted using quantitative research methods. The sample for this research was 300 outpatient patients/prescriptions for indicators of prescription suitability and waiting time, 150 respondents for indicators of customer satisfaction at Pandanarang Boyolali Regional Hospital. The results of the study showed that in the indicator of the length of time for prescription service, the average time for non-concocted prescriptions was 16.33 ± 15,114 minutes and for concocted prescriptions it was 29.85 ± 27,958 minutes, for the patient satisfaction indicator the results were 94.03%, as well as for the indicator The conformity of the prescription with the formulary was 94.72%. Based on the research results obtained, it can be concluded that according to the Decree of the Minister of Health of the Republic of Indonesia Number 129/MENKES/SK/II/2008 concerning Minimum Service Standards for Hospitals in the Pharmaceutical Sector which has been determined by the Ministry of Health of the Republic of Indonesia that the Pandanarang Boyolali Regional General Hospital is in the indicator The conformity of prescriptions with the formulary does not meet standards, the average waiting time for prescription services meets standards, and the level of customer satisfaction with pharmacy services in pharmaceutical installations meets standards